Measuring Employees Awareness and Perception of Green HRM Practices: A Quantitative Study - Malhotra, Prerna; Kaur, Satveer (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In recent years, the banking industry has experienced tremendous growth and investment, with the majority of banks implementing green banking programs. In order to preserve the ecological balance, banks are implementing a variety of environmental practices in their daily operations. Since green banking directly affects the environment, the idea contributes to the creation of a cleaner and greener future. This research paper presents a comprehensive review of employees’ awareness and perception of green human resource management practices. Green banking is an emerging concept in the financial industry that promotes sustainable and environmentally friendly banking practices. The successful implementation of green banking requires the active participation and support of bank employees. Therefore, understanding their awareness and perception is crucial for the effective adoption and integration of green banking practices within financial institutions. This paper examines the existing literature on employees’ awareness and perception of green banking, identifies key factors influencing their attitudes, and explores the potential benefits and challenges associated with promoting green banking within the workforce. A total of 120 bank employees of Punjab National Bank of Solan District received the questionnaire. The approach of random sampling was used. Data Analysis was done by applying Chi-Square test and ANOVA. Findings of the study concluded that majority of the respondents are aware of the Green HRM Practices of the banks.